Implementation of Health Values in Islamic Education - Hidayani, Cut Eliza; Lubis, Syaiful Akhyar; Ritonga, Asnil Aidah (JTP - Jurnal Teknologi Pendidikan, 2025)
Health is one of the gifts and grace given by the creator to humans, with the gift of health, humans can carry out all their activities properly to fulfill all their life needs and their existence. This study aims to analyze the implementation of health education values in Dayah Bustanul Ulum and Dayah Futuhul Ma'arif Al-Aziziyah, focusing on the behavior of students in implementing cleanliness, healthy eating patterns, exercise, and mental health. A qualitative approach with a phenomenological design is used to understand students' understanding of the concept of holistic health that includes physical, mental, and spiritual aspects, which are in accordance with Islamic teachings. Primary and secondary data were collected through interviews, observations, field notes, and documentation, then analyzed through data reduction, presentation, and drawing conclusions. The results of the study indicate that both dayahs have a strong commitment to educating students about healthy living as part of worship and social responsibility. Dayah Bustanul Ulum emphasizes the provision of public health facilities with adequate leadership support and facilities, so that the health culture there is more effectively implemented. Meanwhile, Dayah Futuhul Ma'arif Al-Aziziyah faces challenges in leadership support and limited facilities, which hinder the effectiveness of health program implementation. These findings reinforce the importance of health-conscious leadership, provision of adequate facilities, and integration of health education into the curriculum as effective steps to increase awareness and implementation of healthy living behaviors among students. The conclusion is that the different approaches in these two dayahs reflect variations in the application of health values, such as healthy diet, hygiene, and physical activity, which are based on Islamic principles.